Tax Planning and Tax Avoidance The Effect on the Value of Manufacturing Companies in the Food and Beverage Sub-Sector - Putri Wahyuni; Putri Sari Silaban (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of tax planning and tax avoidance on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Samples were taken as many as 12 companies using purposive sampling technique. The results of the study partially show that tax planning has a significant effect on firm value. The results of the study partially show that tax avoidance has no effect and is not significant on firm value. Simultaneous research results show that tax planning and tax avoidance have a significant effect on firm value. The coefficient of determination (R²) shows that the Firm Value variable can be explained by the tax planning, tax avoidance variables while the rest is explained by other factors such as Profit Persistence and Profitability.